2002
DOI: 10.1029/2001gl014353
|View full text |Cite
|
Sign up to set email alerts
|

Lidar observations of sporadic Na layers over Wuhan (30.5°N, 114.4°E)

Abstract: [1] Based on lidar measurements between March and September 2001, the characteristics of sporadic Na layers (Na s layers) over Wuhan (30.5°N, 114.4°E) are presented. Na s layers were observed on 29 occasions from 275 h observational data. They tended to show a seasonal variation with a maximum occurrence rate in July. The maximum Na density was 24080 cm À3 which was comparable with those observed at low and high latitudes. Different from the observations at all other sites over the world, most Na s layers ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
2
29
0
1
Order By: Relevance
“…This statistical plot excluded those events for which we did not observe the beginning times or ending times. One can find that most of them lasted for about 1-3 h. These results agree with those reported by other sodium lidar groups (Batista et al, 1989;Yi et al, 2002;Gong et al, 2002;Vishnu Prasanth et al, 2007). Figure 3 shows the histogram distribution of the ratio of the falling times versus rising times for the SSL events analyzed in Fig.…”
Section: Instrument Description and Data Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…This statistical plot excluded those events for which we did not observe the beginning times or ending times. One can find that most of them lasted for about 1-3 h. These results agree with those reported by other sodium lidar groups (Batista et al, 1989;Yi et al, 2002;Gong et al, 2002;Vishnu Prasanth et al, 2007). Figure 3 shows the histogram distribution of the ratio of the falling times versus rising times for the SSL events analyzed in Fig.…”
Section: Instrument Description and Data Analysissupporting
confidence: 82%
“…But subsequent observations showed that the mid-latitude deficit was not thought to be real in recent years. For example, measurements in the Eastern Hemisphere, i.e., Tokyo (35 • N) from November 1991 to October 1993 and Wuhan (31 • N) from February 1996 to August 2001, gave a mean occurrence interval of about 10 h per SSL event (Nagasawa and Abo, 1995;Yi et al, 2002;Gong et al, 2002), and measurements in the Western Hemisphere, i.e., Colorado (40.6 • N) from April to June 2002 and June to August 2003, indicated that 65% of days and 19% of hours had SSLs (Williams et al, 2007). These observations showed much higher occurrence rates than those observed at mid-latitude before the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…For guaranteeing a good data quality, all the 5-min density data used here are required to have the detection thresholds less than 200 cm −3 in the entire altitude range of the metal layers (75-110 km). The sporadic Na and Fe layers are often observed at our lidar site near 30 • N (Yi et al, 2002(Yi et al, , 2007Ma and Yi, 2010). They are characterized by a large density enhancement in a narrow altitude range and have no clear-cut relation with the main metal layers.…”
Section: Observational Resultsmentioning
confidence: 99%
“…In addition, simultaneous and common volume lidar observations at 30 • N showed that, 62 % of sporadic Na and Fe (Fe s ) layers occurred in overlapping altitude ranges and moved following almost the same track (Yi et al, 2007). Occasionally, Na s layers could appear at extremely high altitude (above 105 km) (Collins et al, 1996;Yi et al, 2002;Gong et al, 2003;Ma and Yi, 2010;Dou et al, 2013). Through a statistics study, Ma and Yi (2010) have found that Na s and Fe s layers above 105 km at 30 • N occurred mostly during summer and possessed long durations and broad layer widths.…”
Section: Introductionmentioning
confidence: 99%